Influential drivers of the cost-effectiveness of respiratory syncytial virus vaccination in European older adults: a multi-country analysis - Xiao Li; Lander Willem; Caroline Klint Johannesen; Arantxa Urchueguía-Fornes; Toni Lehtonen; Richard Osei-Yeboah; Heini Salo; Alejandro Orrico-Sánchez; Javier Díez-Domingo; Mark Jit; for PROMISE investigators; Joke Bilcke; et al. (BMC Medicine)
Abstract Background We aimed to identify influential drivers of the cost-effectiveness of older adult respiratory syncytial virus (RSV) vaccination in Denmark, Finland, the Netherlands and Valencia-Spain. Methods A static multi-cohort model was parameterised using country- and age-specific hospitalisations using three approaches: (A) the International Classification of Diseases (ICD)-coded hospitalisations, (B) laboratory RSV-confirmed hospitalisations and (C) time-series modelling (TSM). Plausible hypothetical RSV vaccine characteristics were derived from two protein subunit vaccines for adults aged ≥60 years. A full incremental analysis was conducted by comparing three RSV vaccination strategies: (1) in adults aged ≥60 years (“60y+”); (2) in adults aged ≥65 years (“65y+”); (3) in adults aged ≥75 years (“75y+”) to “no intervention” and to each other. Both costs and quality-adjusted life-years (QALYs) were discounted at country-specific discount rates and the analysis was conducted from both the healthcare payers’ and societal perspectives. Value of information, probabilistic sensitivity and scenario analyses identified influential drivers. Results Besides vaccine price, the hospitalisation estimates were most influential: (A) Using adjusted RSV-ICD-coded hospitalisations at a vaccine price of €150 per dose, no intervention was cost-effective up to willingness-to-pay (WTP) values of €150,000 per QALY gained in Denmark and the Netherlands, and up to €124,000 per QALY gained in Finland. (B) Using the adjusted RSV-confirmed dataset, the findings were consistent in Denmark and comparable in Finland. In Spain-Valencia, the 75y+ strategy became cost-effective at WTP >€55,000. (C) Using TSM-based estimates, the 75y+ strategy was cost-effective at WTP >€45,000, >€101,000, >€41,000 and >€114,000 in Denmark, Finland, the Netherlands and Spain-Valencia, respectively. Sensitivity analyses showed that the (in-hospital) case fatality ratio and the specification of its age dependency were both influential. Duration of protection was found more influential than a variety of plausible waning patterns over the duration of protection. Conclusions Data gaps and uncertainties on the RSV-related burden in older adults persist and influence the cost-effectiveness of RSV vaccination. More refined age- and country-specific data on the RSV attributable burden are crucial to aid decision making.